Digital Cultural Heritage and Wikimedia Commons Licenses:: Copyright or Copywrong? - Kelly, Elizabeth Joan (Journal of Copyright in Education & Librarianship, 2019)
Cultural heritage institutions can contribute to public knowledge and increase awareness of their collections by uploading digital objects to Wikimedia Commons for use on Wikipedia and other Wikimedia Foundation projects. However, prior research has established the difficulty of and/or hesitation by many cultural heritage institutions in clearly and accurately labeling the copyright status of their born-digital and digitized collections. With this knowledge, how likely is it that digital cultural heritage will be findable and usable on Wikimedia Commons? This study seeks to determine how accurate rights statements for cultural heritage objects on Wikimedia Commons are, and whether inaccuracies can be linked to problematic rights statements in cultural heritage digital libraries or whether the inaccuracies stem from Wikimedia Commons. By evaluating the rights statements, licenses, and sources for 308 Wikimedia Commons objects from 57 cultural heritage organizations and comparing that information to corresponding licenses from digital libraries, we can begin to develop best practices and educational needs for digital librarians, archives, museum curators, and Wikipedians alike to improve the user experience for those using digital cultural heritage on Wikimedia projects.